Severe Plastic Deformation Techniques - Cabibbo, Marcello (IntechOpen, 2017)
Grain size is recognized as a key microstructural factor affecting mechanical and, to some extent, physical properties of metals and metallic materials. For this reason, all the means designed to control and modify the grain size are considered a proper way to design and tailor metallic materials with desired properties. In this sense, microstructure refinement through severe plastic deformation (SPD) techniques can be considered a key method for this purpose. A typical SPD process is currently defined as any method of metal forming under extensive hydrostatic pressure intended to impose a very high strain on a bulk solid without involving any significant change in the overall dimensions and having the ability to produce exceptional grain refinement. What makes SPD processing techniques so popular and attractive is the possibility of using them to enhance the strength behavior of conventional metallic materials by a factor of up to eight for pure metals such as copper and by some 30-50% for alloys. Despite the impressive property improvement achievable with SPD techniques, their uptake by industry has been rather sluggish. This book intends to give a panorama of the typical SPD techniques intended to optimize the mechanical and physical properties of metals through a significant grain size reduction process. Modeling for this purpose is also presented.